Use of bagasse to remove 2-chlorophenol in aqueous system (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The adsorption method using waste bagasse has been examined to remove 2-chlorophenol (2-CP) from aqueous solutions at room temperature. The adsorption of 2-chlorophenol by bagasse carbon could be studied in batches by changing the contact time, operating temperature, pH of the solution, initial concentration, adsorbent dose, and particle size. It took three hours to reach equilibrium. The Langmuir model correctly predicted the adsorption equilibrium data for 2-chlorophenol-sorbent systems in the concentration range that was examined. When the pH was lower, getting rid of 2-CP from surfaces was easier. Studies of desorption show that chemisorption is an important part of the adsorption process.J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 83-95, June-December 2022